The educational role of intellectual awareness units in Saudi universities in achieving intellectual immunity for its students - Asiri, Retal Muhammad (Journal of Educational and Psychological Sciences, 2023)
The study identifys the educational role of intellectual awareness units in achieving intellectual immunity from the point of view of Saudi university students, and its obstacles. It used the descriptive survey method on a sample of (750) students from five Saudi universities; (Tabuk, Hafr Al-Batin, Princess Noura, King Khalid, and Umm Al-Qura), the society of the study is the whole Saudi Arabia universities which the numbers more over 261961 students. The results showed that the educational role of the intellectual awareness units and obstacles to activating this role in achieving intellectual immunity among students from their point of view came to a medium degree, and there were no statistically significant differences at the level of significance (α
Keywords: Education; Intellectual knowledge; intellectual protection; university stage